2014 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2014
DOI: 10.1109/icassp.2014.6854251
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbolic frequency modulation for multiple users in underwater acoustic communications

Abstract: Nonlinear frequency-modulated signals have been effectively applied in multiple-user communication schemes. In this paper, we propose to implement a multiple-user communication scheme using hyperbolic frequency-modulated (HFM) signals for underwater acoustic communications. We derive constraints on the HFM parameters to optimally reduce multiple access interference (MAI) at the transmission side. Additional constraints on the frequency-modulation (FM) rate reduce the underwater channel effects of multipath and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The construction of a new family of frequency hopping codes called hyperbolic frequency hop codes was given, and it was shown that the hyperbolic frequency hop codes possessed nearly ideal characteristics for use in both types of system. Zhou et al [21] derived constraints on the HFM parameters to optimally reduce Multiple Access Interference (MAI) at the transmission side. Additional constraints on the frequency-modulation rate reduced the underwater channel effects of multipath and scaling.…”
Section: Related Workmentioning
confidence: 99%
“…The construction of a new family of frequency hopping codes called hyperbolic frequency hop codes was given, and it was shown that the hyperbolic frequency hop codes possessed nearly ideal characteristics for use in both types of system. Zhou et al [21] derived constraints on the HFM parameters to optimally reduce Multiple Access Interference (MAI) at the transmission side. Additional constraints on the frequency-modulation rate reduced the underwater channel effects of multipath and scaling.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, multi‐user HFM is also studied in the UWA channel. Multi‐user communication for the UWA channel in [12] is accomplished by using an HFM signal and to reduce MAI different FM rates are used, but the surge in the number of users results in BER degradation, and up to four users can be catered. Recently, the researchers in [13] implemented hyperbolic chirp using pseudo‐random (PN) codes for different users, and orthogonality was maintained using three methods which include Gram–Schmidt iteration, insertion, and multiplication methods, respectively, while at the receiver simple matched filter was used.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the high-temporal correlation, the multiple HFM signals which arrive at the receiver at the same time can be separated using a bank of matched filter. In other words, the different ANs are able to transmit their packet simultaneously without collision [ 8 , 9 ]. Accordingly, the localization performance can be decoupled from the MAC delay.…”
Section: Introductionmentioning
confidence: 99%